PERFORMANCE OF THE FOOD SECURITY OFFICE IN EFFORTS TO STRENGTHEN FOOD SECURITY IN NORTH BENGKULU DISTRICT - Rinchi Yusfit Arputama; Edi Darmawati; Bobby Mandala Putra (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This study aims to describe the performance of the Food Security Service in efforts to strengthen food security in North Bengkulu Regency in terms of performance measurement theory according to Dwiyanto, 2008 (Bintang & Widowati, 2017), namely productivity, service quality, responsiveness, responsibility, and accountability. This type of research is qualitative research. The location of this research is the Food Security Service of North Bengkulu Regency. The informant selection technique for this research was informal snowball sampling. Data collection was carried out through author observation, in-depth interviews, and documentation studies. Data analysis was carried out through descriptive data analysis techniques. The results of this study indicate that the performance of the Food Security Service in an effort to strengthen food security in North Bengkulu Regency is carried out by distributing vegetable seeds for the use of yards. The people of North Bengkulu Regency, both individually and through organizations, can submit applications. The success of this effort is supported by productivity factors, service quality, responsiveness, responsibility, and accountability that are going well. Some of the obstacles in efforts to strengthen food security in North Bengkulu Regency are the lack of a socialization program, geographical constraints, and resource constraints to reach all areas of North Bengkulu Regency.